Penanaman Nilai-nilai Kepedulian terhadap Kebersihan Lingkungan pada Siswa Kelas III di Sekolah Alam Mahira Kota Bengkulu - Evita Sangkut; Puspa Djuwita; Dalifa Dalifa (JURIDIKDAS, 2019)
This study aims to describe "The cultivation of values of Concern on Environmental Hygiene in Students Class III A At the Elementary School of Nature Mahira Bengkulu City". This type of research is using qualitative and qualitative descriptive research method. Research subjects were principal, grade III A teacher, janitor, canteen mother, and third grade student A. Data collection technique used was observation, interview, and documentation. The analysis technique is carried out during field analysis and post-field analysis by examining all data collected in narrative. The data that have been obtained is analyzed by data reduction, data presentation, and conclusion. The data credibility test is done through increasing persistence and triangulation of sources and techniques. The results obtained are: a) The strategy of cultivating the values of caring is done by habituation, exemplary and menjarkan about cleanliness; b) Program activities are: clean culture, clean saturation program, class cleanliness, school environment cleanliness, and waste management; c) Facilities and infrastructure; d) School community support: principals, janitors, and canteen mothers.